2016
DOI: 10.1021/acs.est.6b01741
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from Electronic Cigarettes: Key Parameters Affecting the Release of Harmful Chemicals

Abstract: Use of electronic cigarettes has grown exponentially over the past few years, raising concerns about harmful emissions. This study quantified potentially toxic compounds in the vapor and identified key parameters affecting emissions. Six principal constituents in three different refill "e-liquids" were propylene glycol (PG), glycerin, nicotine, ethanol, acetol, and propylene oxide. The latter, with mass concentrations of 0.4-0.6%, is a possible carcinogen and respiratory irritant. Aerosols generated with vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
377
9
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(441 citation statements)
references
References 27 publications
31
377
9
5
Order By: Relevance
“…Emission factors (ng/h) of selected metals and trace elements during iQOS, EC, and CC consumption. The data corresponding to EC and CC are adopted from Saffari et al (2014 in a number of previous studies (Jensen et al 2015;Gillman et al 2016;Sleiman et al 2016).…”
Section: Aldehydesmentioning
confidence: 99%
“…Emission factors (ng/h) of selected metals and trace elements during iQOS, EC, and CC consumption. The data corresponding to EC and CC are adopted from Saffari et al (2014 in a number of previous studies (Jensen et al 2015;Gillman et al 2016;Sleiman et al 2016).…”
Section: Aldehydesmentioning
confidence: 99%
“…Some of the toxicants found in EC vapour are likely formed as by-products during thermal degradation, especially with high-powered devices (Sleiman et al 2016). For example, Blair et al (2015) discovered detectable levels of acetaldehyde (suspected carcinogen), acrolein (inflammatory agent), and acetone (central nervous system depressant) in EC aerosols, though in lower amounts than in CCs.…”
Section: Composition Of Unflavoured Ec Aerosolsmentioning
confidence: 99%
“…For instance, Farsalinos et al (2015b) detected formaldehyde, acetaldehyde, acetone, and acrolein in EC aerosols; Flora et al (2016) detected formaldehyde but no acetaldehyde or acrolein in EC aerosols; and Goniewicz et al (2015) detected formaldehyde, acetaldehyde, acrolein, and o-methylbenzaldehyde in EC aerosols. Sleiman et al (2016) identified two other potential carcinogens in EC vapour: propylene oxide and glycidol. Other articles showed similar results, with increasing levels of toxicants when higher-powered devices were used (Laugesen 2008;McAuley et al 2012;Goniewicz et al 2014b;Hutzler et al 2014;Kosmider et al 2014;Tayyarah and Long 2014;Geiss et al 2015;Herrington and Myers 2015; Zucchet and Schmaltz 'Connell et al 2015;El-Hellani et al 2016;Jo and Kim 2016;Leigh et al 2016;Sleiman et al 2016;Talih et al 2016).…”
Section: Composition Of Unflavoured Ec Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Propylene glycol when heated may produce propylene oxide, a class 2B carcinogen. 32 Tobacco-specific nitrosamines are highly carcinogenic, but the low levels found in most ENDS products are unlikely to pose a substantial risk. 33 Certain ENDS emissions can impact the viability of established cultured cell lines, however, to a lesser degree than cigarette smoke.…”
Section: Aldehydesmentioning
confidence: 99%